2014
DOI: 10.1021/bk-2014-1166.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Eye Tracking Methodology for Chemistry Education Research

Abstract: Eye tracking has long been a staple research tool in the field of psychology, and has recently begun to see applications in chemistry education research. This chapter will discuss the foundations of eye tracking research, including fundamentals of how eye tracking works, collection and analysis of eye tracking data, and research applications of eye tracking in chemistry education research and related disciplines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 83 publications
1
21
0
Order By: Relevance
“…The use of classroom observations in conjunction with interviews can provide opportunities to check for data alignment (Yezierski provides an excellent review of the use of classroom observation protocols in this volume (45)). Alternatively, in using a think-aloud protocol during the solving of selected problems, a researcher may also choose to use an eyetracking device as measure of how participants read the text of the problem or examine any structures provided (in this volume Havanki and VandenPlas discuss the different ways eye tracking technology can be used in CER (46)).…”
Section: Triangulationmentioning
confidence: 99%
“…The use of classroom observations in conjunction with interviews can provide opportunities to check for data alignment (Yezierski provides an excellent review of the use of classroom observation protocols in this volume (45)). Alternatively, in using a think-aloud protocol during the solving of selected problems, a researcher may also choose to use an eyetracking device as measure of how participants read the text of the problem or examine any structures provided (in this volume Havanki and VandenPlas discuss the different ways eye tracking technology can be used in CER (46)).…”
Section: Triangulationmentioning
confidence: 99%
“…Eye-tracking technology has begun to be applied in CER (45)(46)(47)(48)(49). One of the important variables in eye-tracking studies is scanpath.…”
Section: Permutation Testsmentioning
confidence: 99%
“…Within social science, scientists have studied cognitive development using eye-tracking (Lai et al, 2013). Havanki and VandenPlas (2014) suggested that "eye tracking collects information about eye movements and provides methods for analyzing a viewer's visual attention patterns" (p. 193). Eye tracking can be described using a) fixation, b) fixation duration, c) total fixation duration, d) saccade, e) smooth pursuit, f) regress, and g) scanpath.…”
Section: Introductionmentioning
confidence: 99%
“…Eye tracking can be described using a) fixation, b) fixation duration, c) total fixation duration, d) saccade, e) smooth pursuit, f) regress, and g) scanpath. Fixation describes the process in which an individual pauses and focuses on one thing, and fixation duration and total fixation duration measure fixation length as one measures the total time of fixation during the trial and the other measures the total time of fixation on a specific region of interest (Havanki & VandenPlas, 2014). According to Havanki and VandenPlas (2014), the saccade describes the "rapid eye movements between fixations lasting between 10 ms and 100 ms," and the smooth pursuit describes the "slow eye movements that keep an image stationary on the fovea [central vision]" (p. 194).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation